Information Communication Technologies in Teaching English as a Foreign Language: Analysing EFL Teachers’ TPACK in Czech Elementary Schools - Dev Raj Paneru (Center for Educational Policy Studies Journal)
This qualitative study was carried out in five different elementary schools in the Czech Republic. It aimed to investigate how English as Foreign Language teachers developed teaching competence and practised information communication technology integration in classroom teaching. To this end, this study employed the idea of a Technology Pedagogy and Content Knowledge –TPACK -in-Action Model. It advocates a ‘learning by doing’ approach on (social) construction to better understand how teachers develop technological and/or computer-assisted language learning competency for teaching and practice in an English as a Foreign Language environment. Under this model, this study conducted qualitative analysis and found two different approaches in practice, which were categorised as Formal Practice and Functional Practice. The former involved a conservative mechanical practice of technology use in language teaching whereas the latter involved it in terms of (social) construction. According to analyses based on conservative practices, teachers expressed that mechanical TPACK in association with technology in classes limited the transmission of mechanical knowledge from English texts. In Functional Practice, however, teachers drawing upon alternative learning interactions expressed positive transformation results from TPACK, associated with the use of technologies integrated into class instructions as a collaborative tool for learning models. In these latter integrated practices, teachers’ perceptions, practices, and reflections in combining technologies in an English as a Foreign Language environment, as new literacy skills, identified an increase in the learner’s creative potential.